Reingeniería de procesos para la empresa Auto Shopping de la ciudad de Loja - Erreyes Armijos, Damián Euclander (2016)
The work entitled "Process Reengineering FOR AUTO CITY SHOPPING LOJA" aimed to make a thorough study of the company, especially in terms of processes is concerned; which after a certain study it was able to identify the processes that are currently running in the enterprise, identifying the difficulties encountered each. Bibliographic information for the study with a conceptual framework which was formed to scientifically support this research was compiled. He then proceeded to do a situational analysis of Auto Shopping in the city of Loja, from which it was evident that the company exists since 2001, whose business is selling decorative accessories for all kinds of vehicles. He is currently structured in four areas in which they work nine employees and serve the market of Loja. For information on nine field surveys apply to employees of Auto Shopping, as well as an interview with the manager, in order to identify the processes that need to be restructured. Shopping, Shopping request accessories sales, sale by credit card, Office, receipt of merchandise, payment to suppliers, collection of nonperforming and Operational Procedures: key business processes, including those that are identified. Shopping , Shopping request Sales of accessories, Sale Credit Card , Office, receipt of merchandise , payment to suppliers, collection of nonperforming and Processes Operating in the workshop : the key processes of the company, among which are identified . Each of the current processes that the company Auto Shopping city of Loja was described , then the same analysis was performed. Critical points were identified and reengineering processes are performed as Sales , Installation of Aros, Tire Mounting , installation of sounds , Office clients , Receiving Merchandise purchased and procurement process. To make the reengineering those responsible for each area was named as: Administrative Area Leader : Mr. Juan Echeverria Juan Andres Cuadros • Accounting Area Leader : Evelin Torres. • Area Sales Leader : Ms. Nina Cave , Mr. Juan Echeverria. . • Workshop Leader : Luis Pinta. The redesign of processes is performed ; Sales , Installation of Aros, Tire Mounting , installation of sounds , Office clients , Receiving Merchandise purchased and procurement process. As a result of the redesign a reduction of 143 min for the procurement process, saving 3 min to the sales process , receipt of merchandise to 135 min of difference with the redesigned process , installation of new rings with a time of 48 min was obtained apart like the rim assembly , the current processes . It should be noted that the company Auto Shopping city of Loja reengineering of the aforementioned processes is required , enabling efficient and effective , making better use of resources.